Pengaruh Media Sosial Instagram Terhadap Kewaspadaan Masyarakat: (Studi Kasus Pada Akun Instagram @Depok24jam) - Aristian Kurniawan Pratama; Amalia Azmi Sitorus (Pusat Riset dan Inovasi Nasional, 2024)
Over the years, Depok has been negatively portrayed by its many social problems. Undoubtedly, this social problem must be anticipated as a warning to the community. Instagram is a type of social media that has the ability to increase public awareness through the dissemination of content. The purpose of this research is to find out how much influence the social media account Instagram @depok24jam has on people's awareness in Depok City. The design of this study used a quantitative method by collecting data using an online questionnaire (G-Form) on 100 sample respondents following the Instagram account @Depok24Jam. Data were analyzed using the Simple Linear Regression Analysis technique with descriptive testing, validity, reliability, normality, linearity and linear regression lines. The results and conclusions of the study found that Social Media Instagram @depok24jam had a significant influence on Community Alertness with a Sig value. 0.000 <0.05 and Tcount > Ttable 8.436 > 1.661. Researchers provide advice to the Instagram account @depok24jam, any content uploaded by the @depok24jam account is based on verifiable facts and comes from trusted news sources. Avoid spreading false or unverified information, as this can undermine the credibility of the account. And try to be the leading source of information in the Depok area.